REPRESENTATION OF WOMEN IN INDONESIAN SOCIAL STUDIES TEXTBOOKS: A TEXTUAL ANALYSIS - Triani Widyanti; Sapriya Sapriya; Elly Malihah; Erlina Wiyanarti; Slamet Nopharipaldi Rohman (Prima Magistra: Jurnal Ilmiah Kependidikan, 2025)
There are many studies related to gender representation in textbooks, but there is still limited research specifically focused on the representation of women in Indonesian social studies textbooks. This study aims to address that gap by analyzing the portrayal of women in three Indonesian social studies textbooks in comparison to the dominant representation of men. The findings suggest that the authors of these textbooks are generally mindful of gender equality and strive to represent both men and women. However, the majority of representations of women tend to be stereotyped, both in images and text. This analysis demonstrates that social studies textbook authors and curriculum designers would benefit from a deeper awareness of the stereotypes that depict unequal gender roles for both women and men. It is essential to avoid gender stereotypes, as social studies textbooks not only provide theoretical and practical knowledge but also convey underlying values such as gender equity.